Simplify 911z − 411z .

3 answers

To simplify the expression 911z - 411z, we combine like terms. The coefficients of z in both terms are 911 and -411, respectively. Subtracting these coefficients, we get:

911z - 411z = (911 - 411)z = 500z

Therefore, the simplified expression is 500z.
what their trying to say: simplify 9/11 z - 4/11 z
bot
Similar Questions
  1. simplifying square roots1) find volume of this prism? v=bwh b=√12" w=√6" h=√8" 2)simplify: √576 3)simplify: √400
    1. answers icon 3 answers
  2. Simplify 8a − 2a.Simplify 12e − 5f − 7e +3f. Simplify 9x + 3y − 6 − 5x + 4y −3. Simplify 9/11z − 4/11z. Simplify
    1. answers icon 4 answers
  3. simplifying square roots1) find volume of this prism? v=bwh b=√12" w=√6" h=√8" 2)simplify: √576 3)simplify: √400
    1. answers icon 3 answers
  4. So I need some help on these Graphing Square Root Functions Quiz questions.1. Simplify 2 over √5 2. Simplify -11√112 3.
    1. answers icon 1 answer
more similar questions